Making it to the finish line: educational resilience among Dominican women of Haitian descent - Salusky, Ida; Tull, Mary (Informa UK Limited, 2021)
Dominican-born children of Haitian descent are frequently excluded from the public education system in the Dominican Republic. Barriers to participation include poverty, discriminatory government policies, and structural barriers within school settings. Females of Haitian descent face additional barriers due to gender discrimination. The current study used modified grounded theory to analyze qualitative interviews from 32 Dominican females of Haitian descent to explore factors that promote and impede educational resilience. Barriers to school participation included: the economics of school integration and persistence, poor cultural and learning climate within school, and limited structural supports for female students who want to pursue education while pregnant, or raising children. Factors described as promoting educational resilience included: successfully balancing work and study from an early age, having supportive social networks, and holding strong beliefs about the future value of education. Findings challenge and inform dominant discourses about factors that impede and support educational resilience.
Keywords: Educational inequality; educational resilience; persistence; social support; young motherhood